Increasing incomes and reducing post-harvest losses in Mbulu [Tanzania] - Mjawa, Bertha (Technical Centre for Agricultural and Rural Cooperation, 2018)
In the Bashay valley, Tanzania, farmers have received help to purchase processing equipment , and training on post-harvest management technologies and packaging materials, to reduce post-harvest losses and increase their income by processing their garlic crop. The creation of a consortium for the garlic value chain is also helping to strengthen and coordinate the sector.